2014
DOI: 10.1021/pr500691a
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Applicability of Antibodies Generated within the Human Protein Atlas as Capture Agents in Immunoenrichment Coupled to Mass Spectrometry

Abstract: For identification and characterization of proteins in complex samples, immunoenrichment coupled to mass spectrometry is a good alternative due to the sensitivity of the affinity enrichment and the specificity of mass spectrometry analysis. Antibodies are commonly used affinity agents; however, for high-throughput analysis, antibody availability is usually a bottleneck. Here we present a protocol for immunoenrichment coupled to mass spectrometry in a high-throughput setup, where all steps from bead coupling to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…[ 146 ] Other initiatives such as the HPA have demonstrated that polyclonal antibody repertoire, generated towards protein fragments, can be used for peptide enrichment together with spike in of heavy labeled protein fragment standards. [ 147 , 148 ]…”
Section: Potentials and Challenges Of Affinity-based Proteomicsmentioning
confidence: 99%
“…[ 146 ] Other initiatives such as the HPA have demonstrated that polyclonal antibody repertoire, generated towards protein fragments, can be used for peptide enrichment together with spike in of heavy labeled protein fragment standards. [ 147 , 148 ]…”
Section: Potentials and Challenges Of Affinity-based Proteomicsmentioning
confidence: 99%
“… 18 Antibodies are most widely used for this purpose due to their availability, their use in ligand binding assays, and the often high affinity and specificity for their targets. 19 , 20 However, antibodies come with a number of challenges such as an expensive and lengthy production process, possible cross-reactivity, 21 and issues with batch-to-batch variability. 20 To address these limitations, other antibody-based binders such as fragment antigen-binding (Fab) and single-chain variable fragments (scFv) have been designed, 22 as well as a range of nonantibody-based binders, comprising aptamers, avimers, knottins, DARPins, and Affimer reagents.…”
Section: Introductionmentioning
confidence: 99%
“…Affinity enrichment involves the use of capturing agents or binders to selectively bind these proteins . Antibodies are most widely used for this purpose due to their availability, their use in ligand binding assays, and the often high affinity and specificity for their targets. , However, antibodies come with a number of challenges such as an expensive and lengthy production process, possible cross-reactivity, and issues with batch-to-batch variability . To address these limitations, other antibody-based binders such as fragment antigen-binding (Fab) and single-chain variable fragments (scFv) have been designed, as well as a range of nonantibody-based binders, comprising aptamers, avimers, knottins, DARPins, and Affimer reagents. , Affimer reagents are a group of alternative binding proteins, which possess two variable binding loops inserted into the human protease inhibitor stefin A or phytocystatin protein scaffolds.…”
Section: Introductionmentioning
confidence: 99%
“… Champion dual Ab-capture with MS identification: Enhance the accuracy of Ab-based epitope/antigen detection by confirmation using high-accuracy, high-stringency MS identifications across real-life spatio-temporal biological settings. Collectively, there is recognition within the HPP that future stringent co-registration of MS with Ab data are required to achieve the ultimate spatio-temporal human proteome expression atlas 180 . Exploit massively parallel MS 174 to increase throughput: For rapid, sensitive and higher-throughput MS analysis.…”
Section: Discussionmentioning
confidence: 99%